Molecular Simulation Analysis of Polyurethane Molecular Structure under External Electric Field - Zhiyi Pang; Shangshi Huang; Yi Li; Yiyi Zhang; Rui Qin (Molecules, 2024)
Polyurethane (PU) materials are extensively utilized in power equipment. This paper introduces a comprehensive evaluation method that combines electromagnetics and computational chemistry based on the Density Functional Theory (DFT) to elucidate the impact of external electric fields on the molecular structure of PU during electrical contact. The study focuses on the microstructural and molecular energy changes in the hard (HS) and soft (SS) segments of PU under the influence of an electric field of uniform intensity. Findings indicate that the total energy of HS molecules decreases markedly as the electric field intensity increases, accompanied by a significant rise in both the dipole moment and polarizability. Conversely, the total energy and polarizability of the SS molecules decrease, while the dipole moment experiences a slight increase. Under the influence of a strong electric field, HS molecules tend to stretch towards the extremities of the main chain, leading to structural instability and the cleavage of hydroxyl O-H bonds. Meanwhile, the carbon chain of the SS molecules twists towards the center under the electric field, with no chemical bond rupture observed. At an electric field intensity of 8.227 V/nm, the HOMO-LUMO gap of the HS molecule narrows sharply, signifying a rapid decline in the molecular structure stability, corroborated by infrared spectroscopy analysis. These findings offer theoretical insights and guidance for the modification of PU materials in power equipment applications.